A genetic approach for microbial electrosynthesis system as biocommodities production platform - Shin, Hyo Jeong; Jung, Kyung A.; Nam, Chul Woo; Park, Jong Moon (Bioresource technology, 2017)
•Microbial electrosynthesis is promising technology as biocommodities production.•Extracellular electron transfer is key point of microbial electrosynthesis.•Genetic engineering can solve the problems of microbial electrosynthesis.•This article proposes recommended host cells. Microbial electrosynthesis is a process that can produce biocommodities from the reduction of substrates with microbial catalysts and an external electron supply. This process is expected to become a new application of a cell factory for novel chemical production, wastewater treatment, and carbon capture and utilization. However, microbial electrosynthesis is still subject to several problems that need to be overcome for commercialization, so continuous development such as metabolic engineering is essential. The development of microbial electrosynthesis can open up new opportunities for sustainable biocommodities production platforms. This review provides significant information on the current state of MES development, focusing on extracellularly electron transfer and metabolic engineering.